Dynamic voltage attenuation identifies atrial fibrosis in a rabbit model: simultaneous assessment with optical mapping and contact electrogram mapping. (19th May 2022) - Sim, I; O'neill, L; Whitaker, J; Mukherjee, R; O'hare, D; Fitzpatrick, N; Niederer, S; O'neill, M; Shattock, M; Williams, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation. Academy of Medical Sciences. Background: Bipolar voltage amplitude is a widely-used clinical parameter in atrial electrophysiology procedures. However, voltage amplitude is variable, and it has been shown that increasing activation rate decreases bipolar voltage amplitude in patients with atrial fibrillation. It is not known whether such voltage attenuation is a marker of the presence of atrial fibrosis which could therefore be used to improve intra-procedural assessment of atrial cardiomyopathy. Purpose: We sought to investigate the effect of increasing activation rate on bipolar voltage amplitude in both healthy and fibrotic left atrial tissue. Methods: 10 New Zealand Rabbits were fed a high cholesterol diet (0.75%) for a period of 12 weeks to create an atrial fibrosis model. 10 Animals were fed normal chow. After terminal anaesthesia the heart was excised, and optical and voltage mapping of the excised left atrial tissue was performed. Blebbistatin was used to maintain cardiac stasis and the voltage sensitive dye RH237 was used for optical mapping. Voltage and optical recordings were made during pacing was from 3 different directions at rates from 2-6Hz and at 3 sites across the atrial tissue. Voltage amplitude was recorded as the mean amplitude over 10 beats during steady-state pacing. Optical recordings were used to measure conduction velocity and action potential characteristics. Only pacing runs showing 1:1 conduction were included in analysis. Atrial fibrosis was assessed using Masson's Trichrome staining. Results: The degree of atrial fibrosis was significantly greater in the atrial fibrosis model compared to healthy controls (15±3.24% vs. 9.74±4.98%, p=0.0069). Median voltage at base rate pacing of 2Hz was not significantly different between control and fibrotic atria (11.63mV, IQR 6.35mV vs. 10.3mV, IQR 6.81mV, p=0.71, respectively). Median voltage was significantly lower at 6Hz than at 2Hz in the control group (9.84mV, IQR 6.87mV, p=0.046). The degree of voltage attenuation between study groups was not significantly different between when pacing at 3hz or 4hz, whereas pacing at 5Hz and 6Hz showed significantly greater attenuation in fibrotic atria. At 5Hz the median reduction in amplitude from baseline in control vs fibrotic atria was 0.88mV, IQR 2.36mV vs 1.92mV, IQR 1.63mV (p=0.031). At 6 Hz the median reduction was 0.94mV, IQR 1.69mV vs 2.68mV, IQR 1.11mV, p=0.013 in control and fibrotic groups respectively. Discussion: High cholesterol diet increased atrial fibrosis in a rabbit model. Bipolar voltage amplitude attenuation occurred in both control and fibrotic atria however the degree of voltage attenuation was significantly greater in fibrotic atria. These findings support the further evaluation of dynamic voltage attenuation for intraprocedural identification of atrial fibrosis.